Implementation of the INTERGROWTH‐21st Project in the UK. (16th May 2013) - Roseman, F; Knight, HE; Giuliani, F; Lloyd, S; Di Nicola, P; Laister, A; Roseman, S; Kennedy, K; Burnham, O; Patel, B; Puglia, F; Blakey, I; et al.
Abstract : Please cite this paper as: Roseman F, Knight H, Giuliani F, Lloyd S, Di Nicola P, Laister A, Roseman S, Kennedy K, Burnham O, Patel B, Puglia F, Blakey I, Cheikh Ismail L, for the International Fetal and Newborn Growth Consortium for the 21 st Century (INTERGROWTH‐21 st ). Implementation of the INTERGROWTH‐21 st Project in the UK. BJOG 2013; 120 (Suppl. 2): 117–122. There are approximately 10 000 births per year in the county of Oxfordshire in the UK, which is one of the two European sites for the International Fetal and Newborn Growth Consortium for the 21 st Century (INTERGROWTH‐21 st ) Project. The samples for both components of the project – the Fetal Growth Longitudinal Study (FGLS) and Newborn Cross‐Sectional Study (NCSS) – were drawn from the John Radcliffe Hospital, a major university hospital with a large regional role that covers more than 75% of deliveries in the county. Special activities to encourage participation in this population included the formation of a research coalition to streamline recruitment in the Maternity Unit and the distribution of study information leaflets to women using the hospital's antenatal care service. This was a demanding project and several challenges were overcome to reach recruitment targets and to maintain high standards of data quality. Amongst the major challenges for FGLS at this study site was the level of ineligibility because of maternal age, smoking and body mass index (BMI) ≥ 30. The major challenge for the NCSS field teams was to ensure that all anthropometric data were collected before the early discharge of uncomplicated deliveries, often within 6 hours of birth. It is evident from our experience in implementing this project that, when large‐scale clinical studies are meticulously planned and avoid major disruption to routine clinical care, they are well received by hospital staff and can contribute to the improvement of the overall standard of clinical care.